Anti-bacterial robust Ag@PDA/PEN electrospinning nanofibrous membrane for oil-water separation. (February 2023) - Wang, Pan; Wang, Mengxue; Song, Tao; Chen, Jiaqi; Liu, Xidi; Liu, Xiaoyang; You, Yong; Song, Huijin; Li, Kui; Li, Ying; Feng, Wei; Yang, Xulin
Abstract: Separating of oil-water emulsions under harsh conditions is a major challenge for membrane-based filtration systems. In this study, a well-stabilized electrospinning nanofibrous membrane was successfully fabricated by combining a high-performance engineering polyarylene ether nitrile (PEN) with polydopamine (PDA), and silver nanoparticles (Ag NPs). The employed PEN has comprehensive performance in thermoresistant, anti-corrode and mechanical properties, which was expected to be a robust polymer matrix. Ag NPs were loaded on PEN electrospinning nanofibrous membranes via PDA coating and in situ growth. Morphological measurements revealed a hierarchical structure of fabricated Ag@PDA/PEN membrane with Ag NPs formed in situ covered on the surface. The particle size of Ag NPs was mainly in the range of 50–85 nm and the diameter of PEN fiber was located at∼0.39 μm. The water contact angle (CA) of membranes increased from 30 o to 130 o by the increasing Ag NPs formation. As a result, the prepared composite membranes reached 4978.71 L/m 2 h and 99 % for permeate flux and good retention rate for oil-water emulsion separation, respectively. Moreover, the high-performance PEN further endowed the tough stability and durability of the obtained composite membranes, which can tolerate corrosive emulsions, resist high temperatures, and maintain a high separation efficiency after cycle reuse. Furthermore, the as-prepared membranes demonstrated excellent anti-bacterial properties (>99.99 %) inherited from the introduction of Ag NPs. Therefore, the comprehensive anti-corrode, anti-heat, and anti-bacterial performance provide the fabricated robust Ag@PDA/PEN electrospinning nanofibrous membrane a broad prospect for purifying water resources, especially industrial wastewater treatment under harsh conditions. Highlights: A multifunctional Ag@PDA/PEN electrospinning nanofibrous membrane has been developed by firmly anchored PDA and Ag NPs. The modified nanofibrous membrane exhibited high emulsion flux and oil rejection efficiency as a water-selective membrane. Ag@PDA/PEN electrospinning nanofibrous membrane is durable under harsh corrosion and high temperature environments. Ag@PDA/PEN electrospinning nanofibrous membrane possess excellent anti-bacterial performance.